Addressing Unintended Instructional Messages About Repeated Reading. (10th July 2017) - Frey, Nancy; Fisher, Douglas
Abstract: The authors analyzed 88 classroom observations to determine whether there were actions that teachers were taking to send a message to students that rereading was not valuable. They identified three practices during shared reading, guided reading, and independent reading that telegraphed messages to students against rereading. The authors also observed teachers building repeated reading into their instruction as they changed the purpose, asked really good questions, pressed for evidence, and provided an audience for students.